Operationalizing the Health and Education : Millennium Development Goals in Central Asia, Volume 1, Kyrgyz Republic Health and Education Case Studies - World Bank (Washington, DC, 2012)
The objective of this report is to present a generic framework for analysis and policy action for fuller attainment of the health and education Millennium Development Goals (MDGs) in Central Asia. The framework focuses on the service delivery aspects of achieving the MDGs and emphasizes: a) monitoring outcomes to identify groups which are not achieving MDGs, b) identifying interventions which are effective in raising MDG performance, c) targeting interventions to groups which are not meeting MDGs, and d) strengthening incentives to service providers and users to raise MDG outcomes for these groups. The framework is illustrated with case studies on health and education in the Kyrgyz Republic. As the cases studies show, application of the approach requires good information on the status o f MDG attainment, and the constraints to fuller attainment - including, crucially, qualitative dimensions of MDG attainment, and resource constraints. The Kyrgyz Republic was chosen to illustrate the framework because prior analytical and project work provide a relatively rich base of knowledge and experience and because there is significant government ownership of the key principles involved in the approach. The case studies do not aim to present new analysis of the technical issues in the health and education sectors in the Kyrgyz Republic. Rather, they aim to bring together relevant existing sector knowledge and lessons of experience in order to derive the options for moving ahead more aggressively on MDG attainment in the health and education sectors.